IMPLEMENTASI MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP TERPADU AL-ITTIHADIYAH - Farhan Sopian Sahid; Fuad Ahmad Riva'i (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2023)
The quality of education is always directly proportional to the quality of learning that involves a teacher and their students. Among the indicators of quality learning is the ability to develop the potential and talents of students. Therefore, learning activities must be planned and designed as best as possible, taking into consideration the students' basic competencies, the weight of the material, the supporting learning media, and most importantly, the method or model of learning that will be used. One of the problems that often occurs nowadays is the lack of active student involvement in the learning process, which leads to low learning motivation and weak creative abilities, ultimately affecting the learning outcomes that can be achieved by the students. Based on initial observations, the main causes of low motivation and learning outcomes are the use of monotonous and conventional learning methods and models, such as continuous lecturing. Therefore, based on this problem, there is a need for improvement to enhance student learning outcomes by using other methods, such as discovery learning. Thus, this classroom action research is conducted with the aim of improving and enhancing learning outcomes using the discovery learning model. The method used in this research is classroom action research, which is a form of reflective research conducted by teachers through specific actions to improve the process and learning outcomes of students. The subjects of this research are the seventh-grade students in the Islamic Education subject, totaling 21 students. Before conducting this action research, a pretest was conducted to determine the initial abilities of the students. The results of the pretest showed that the level of mastery was only 38%. After that, the implementation of the action was carried out, which involved the application of the discovery learning method in cycle I. During this activity, the researcher conducted observations with the assistance of a peer as an observer. The observation results in cycle I showed that the teacher's activity was 70.6% and the student's activity was 68.7%. Then, a test was conducted, and the results showed an improvement compared to before, with a mastery level of 70.6% and a good category. After reflection, the research process continued to cycle II to address the weaknesses and shortcomings identified in cycle I. In this stage, data collection was also conducted through observations and tests. The observation results showed that the teacher's activity was 95.3% with a very good category, while the student's activity was 90.6% with a 100% mastery level. Therefore, it can be concluded that the discovery learning model can improve student learning outcomes